Effect of FeCl3 fixed on silica-gel as catalyst on olives and olive-oil washing wastewaters treatment by photo-Fenton - Hodaifa, Gassan; Rodríguez Pecino, Manuel (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2017)
Motivation: The high production of olive oil in Spain generates a large amount of wastewaters from washing of olives and oil which are currently stored in accumulation rafts for its evaporation. These wastewaters (OMWs) are an environmental problem because they have high organic load with inhibitory compounds as phenols. In this work, photo-Fenton reaction (chemical oxidation) has been used for OMWs treatment. Solid catalyst "FeCl3 fixed on silica-gel" has been used on the photo-Fenton reaction to test its effectiveness on the treatmeant of OMWs. Methods: In all experiments crude OMW (mixed of olives and olive-oil washing wastewaters) with initial COD 16500 g O2/L and TOC = 4942 mg/L are used. In all cases reactor capacity was 1 L. The development of the photo-Fenton experiments was carried out using a FeCl3 fixed on silica-gel as catalyst. Different catalyst concentrations (0.01, 0.1, 0.5, 5, 20 and 25 g/L) are tests. Commun operating conditions are: [H2O2] = 0.024 g/L, T = 20°C, pH = 3, and artificial UV-light. During experiments the quality of treated water was determined by measuring total carbon "TC", total organic carbon "TOC", total nitrogen "TN", chemical oxgen demand "COD", total phenol compounds "TFCs", total iron, turbidity and electrical conductivity. Control experiment has been carried in the same operating conditions but without iron catalyst. Results: In all experiments, the perecentages of organic load removal by photo-Fenton reaction (CODremoval = 48.3-73.5%, TOCremoval = 40.1-87.5%, TFCsremoval = 82.6-93.5% and turbidityremoval = 87.8-93.6%) were determined. Conclusions: The use of photo-Fenton shows high efficiency in the treatment of the olive oil mill wastewater. The photodegradation using the system of UV/H2O2 has a similar results to that obtained by UV/FeCl3/H2O2 system when use 0.01 g/L as catalyst